HUBUNGAN KETERATURAN PEMERIKSAAN ANC TERHADAP KEJADIAN ANEMIA DI WILAYAH KERJA PUSKESMAS TURIKALE KECAMATAN TURIKALE KABUPATEN MAROS - Akib, Resky Devi (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Regular pregnancy checks will determine the mother's health status during pregnancy because basically the cause of Fe deficiency anemia in pregnant women is caused by two factors, namely direct and indirect factors. Meanwhile, factors that do not directly influence a person's Hb levels by influencing the availability of Fe in food include the low economy.The aim of this research is to determine the relationship between the regularity of ANC examinations and the incidence of anemia in the Turikale Community Health Center Working Area, Turikale District, Maros Regency. The type and research method used is the Cross Sectional Study method. In this study, the samples taken were 36 third trimester pregnant women who had their pregnancies checked in the Turikale Community Health Center Working Area, Maros Regency, using purposive sampling. The research results showed that 29 people (80.6%) regularly made ANC visits and 7 people (19.4%) did not regularly. Six respondents (16.7%) experienced anemia and 30 respondents (83.3%) did not experience anemia. There is a relationship between the regularity of ANC visits and the incidence of anemia with a value of ρ=0.004<from α=0.05, this means that Ho is rejected and Ha is accepted. It is hoped that it can increase monitoring and screening of pregnant women who experience high levels of anemia through home visits, making class activities more effective for pregnant women and empowering families, especially husbands or parents, to be motivated to invite pregnant women to have their pregnancies checked regularly. The husband or closest family member can be given an understanding of the dangers and efforts to prevent anemia in pregnant women